Synthesis, ex Vivo and in Vitro Hydrolysis Study of an Indoline Derivative Designed as an Anti-Inflammatory with Reduced Gastric Ulceration Properties - Chin, Chung Man [UNESP]; dos Santos, Jean Leandro [UNESP]; Oliveira, Ednir Vizioli [UNESP]; Blau, Lorena [UNESP]; Menegon, Renato Farina [UNESP]; Peccinini, Rosangela Goncalves [UNESP] (Molecular Diversity Preservation International-mdpi, 2009)
The compound 1-(2,6-dichlorophenyl)indolin-2-one (1), planned as a pro-drug of diclofenac (2), was easily synthesized in 94% yield by an intramolecular reaction in the presence of coupling agent (i.e., EDC). Compound 1 showed anti-inflammatory and analgesic activity without gastro-ulcerogenic effects. The chemical and enzymatic hydrolysis profile of the lactam derivative 1 does not indicate conversion to diclofenac (2). This compound is a new non-ulcerogenic prototype for treatment of chronic inflammatory diseases.
Keywords: indolinone; pro-drug; anti-inflammatory; hydrolysis; diclofenac